Using monitoring and evaluation to build equity and resilience: lessons from practice - Karen A Kotschy; Ancois Carien de Villiers; Michelle Hiestermann; Paulose Mvulane; Glenda Raven; Sue Soal (Ecology and Society, 2025)
The field of monitoring and evaluation (M&E) is intimately connected with issues of power. Power is exercised in choices regarding what is monitored and evaluated; by, for, and with whom this is done; how data are collected; which criteria are used to indicate success; with whom results are shared and for what purpose; and who learns what in the process. M&E findings play a crucial role in determining whether funding and support for initiatives and organizations are continued or stopped. Therefore, the way in which M&E is practiced can profoundly influence whether it promotes equity and resilience or, conversely, dominance, exclusion, and dependency. This paper presents four insights into how M&E practice can contribute to building equity and resilience. These insights are drawn from the authors’ reflections on their experiences as practitioners, facilitated through participation in a Southern African Resilience Academy M&E working group. The working group provided an opportunity to shift practice into knowledge, contrasting with the more commonly used concept of shifting knowledge into practice. Six case studies were used to reflect on successful and unsuccessful aspects within the often messy, contested, and resource-limited contexts of organizations and projects. The paper identifies possible systemic leverage points for building transformative equity and resilience through M&E.